Ação da aplicação intraluminal de glutamina e n-acetilcisteína no estresse oxidativo do tecido intestinal durante isquemia e reperfusão hepática : estudo experimental em ratos - Araújo Filho, Adalzízio Vieira de (2014)
Tissue ischemia followed by reperfusion leads to a series of organic disorders known by ischemia and reperfusion injury , wich are determined by the production of reactive oxygen species. These reactive oxygen species lead to depletion of antioxidant physiological mechanisms and damaging events known as oxidative stress. To reduce such effects, substances with antioxidant activity come with great therapeutic potential. Among them stand out glutamine and n-acetylcysteine. Objective: Analyze the effect of enteral glutamine and n-acetylcysteine injection on oxidative stress caused by ischemia and reperfusion injury intestinal in rats. Method: Male Wistar rats (n=40) were operated for making closed loop in the small intestine, followed by hepatic hilar clamping for 10 minutes and then 5 minutes of reperfusion. In the small intestine closed loop was injected glutamine (glutamine group, n=10), n-acetylcysteine (n-acetylcysteine group, n=10) or distilled water (control group, n=10). Was not conducted ischemia and reperfusion injury or injection of any substance in ten animals (sham group). After reperfusion, has been realized surgical resection of the intestinal closed loop for dosing oxidative stress markers directly in intestinal tissue (malondialdehyde, reduced glutathione, total antioxidant capacity, carbonyls protein, myeloperoxidase, reductase glutathione and peroxidase glutathione). Results: Markers of oxidative injury with representation of gravity by rising values (malondialdehyde and carbonyls protein ) showned lower values in glutamine and n n- acetylcysteine groups compared to control group, respectively, 0,0305 vs. 0,094; and 0,0449 vs. 0,094 (p<0,05). About markers whose gravity was representaded by decrease in values (total antioxidant capacity, reductase glutathione and peroxidase glutathione), the evaluation showed increased values on glutamine and n-acetylscysteine groups compared with the control group, respectively, 13,6143 vs. 5,9712 and 11,7021 vs. 5,9712 to total antioxidant capacity; 6,714 vs. 2,8482 and 5,5771 vs. 2,8482 to reductase glutathione; 4,541 vs. 2,1201 and 3,4040 vs. 2,1201 to peroxidase glutathione (p<0,05). There was exception for reduced glutathione, whose XVIII concentrations were higher only in n-acetylcysteine group (p<0,05). Was not identified myeloperoxidase activity. Conclusion: The enteral injection of glutamine or n-acetylcisteine is related to a intestinal tissue protection during isquemia/reperfusion, because it determines lower cellular structure damages, evaluated for its antioxidant capacity.